Genetic risk variants associated with in situ breast cancer. Issue 1 (December 2015) - Campa, Daniele; Barrdahl, Myrto; Gaudet, Mia; Black, Amanda; Chanock, Stephen; Diver, W.; Gapstur, Susan; Haiman, Christopher; Hankinson, Susan; Hazra, Aditi; Henderson, Brian; Hoover, Robert; et al.
Abstract Introduction Breast cancer in situ (BCIS) diagnoses, a precursor lesion for invasive breast cancer, comprise about 20 % of all breast cancers (BC) in countries with screening programs. Family history of BC is considered one of the strongest risk factors for BCIS. Methods To evaluate the association of BC susceptibility loci with BCIS risk, we genotyped 39 single nucleotide polymorphisms (SNPs), associated with risk of invasive BC, in 1317 BCIS cases, 10, 645 invasive BC cases, and 14, 006 healthy controls in the National Cancer Institute's Breast and Prostate Cancer Cohort Consortium (BPC3). Using unconditional logistic regression models adjusted for age and study, we estimated the association of SNPs with BCIS using two different comparison groups: healthy controls and invasive BC subjects to investigate whether BCIS and BC share a common genetic profile. Results We found that five SNPs (CDKN2BAS -rs1011970, FGFR2 -rs3750817, FGFR2 -rs2981582, TNRC9 -rs3803662, 5p12-rs10941679) were significantly associated with BCIS risk (P value adjusted for multiple comparisons <0.0016). Comparing invasive BC and BCIS, the largest difference was forCDKN2BAS -rs1011970, which showed a positive association with BCIS (OR = 1.24, 95 % CI: 1.11–1.38, P = 1.27 x 10−4 ) and no association with invasive BC (OR = 1.03, 95 % CI: 0.99–1.07, P = 0.06), with aP value for case-case comparison of 0.006. Subgroup analyses investigating associations with ductal carcinoma in situ (DCIS) found similar associations, albeit less significant (OR = 1.25, 95 % CI: 1.09–1.42, P = 1.07 x 10−3 ). Additional risk analyses showed significant associations with invasive disease at the 0.05 level for 28 of the alleles and the OR estimates were consistent with those reported by other studies. Conclusions Our study adds to the knowledge that several of the known BC susceptibility loci are risk factors for both BCIS and invasive BC, with the possible exception of rs1011970, a putatively functional SNP situated in theCDKN2BAS gene that may be a specific BCIS susceptibility locus.